(untitled) (KYAMC Journal, 2017)
Background: Husking, Major and Automatic types of rice mills are small scale industry abundant in Bangladesh producing parboiled rice. A little information is available about the chronic respiratory health problems of the workers due their occupational exposure to the rice mill dust in Bangladesh. Objectives: To be aware of symptoms of chronic respiratory health problems in rice mill workers of Bangladesh. Materials and methods: This descriptive cross sectional study was carried out among 500 rice mill workers. Data were collected about the symptoms of chronic respiratory health problems by face to face interview with questionnaire. Physical examinations and lung function test were done. Results: Total 34.0% of workers complained suffering from the symptoms of chronic respiratory illness. Cough (18.0%), dyspnoea (10.0%), rhinitis (6.8%) and wheezing (5.8%) were the prevalent symptoms. No clinical sign of any respiratory disease was detected. The majority (69.0%) of the symptom sufferers worked in Parboiling and drying section (PBDS) of the mills and their duration of employment and suffering from symptoms were also short. Conclusion: Occupational respiratory health problem in rice mill workers in Bangladesh is not at remarkable level. Only symptomatic treatment is required to elude the problems at present but continuing in job health education, supervision and monitoring are essential for future. KYAMC Journal Vol. 7, No.-2, Jan 2017, Page 758-761